Collapse of the endemic lizard Podarcis pityusensis on the island of Ibiza mediated by an invasive snake. Issue 3 (11th March 2021) - Montes, Elba; Kraus, Fred; Chergui, Brahim; Pleguezuelos, Juan M
Abstract: The invasive snake Hemorrhois hippocrepis colonized the island of Ibiza (Balearic Islands) in 2003 as stowaways inside trunks of olive trees imported for gardening. It has quickly spread since 2010, posing a threat to the island's only remaining endemic vertebrate, the Ibiza wall lizard Podarcis pityusensis . We map the yearly expansion rate of the snake and estimate via transect surveys how severely it affects the distribution and abundance of the endemic lizard. As well, we surveyed 9 of 30 small lizard populations on islets surrounding Ibiza that have been isolated since the Last Glacial Maximum. Snakes had invaded 49% of Ibiza's land area by 2018, and censuses show a critical contrast in lizard abundance between areas with and without snakes; almost all censuses in areas without snakes show lizard presence whereas nearly all censuses in areas with H. hippocrepis lack lizard sightings. Moreover, at least one subspecies previously thriving on one of the offshore islets has become extinct, and there have been several snakes recorded swimming between Ibiza and the surrounding islets. Therefore, lizard populations have been dramatically reduced or have vanished within the range of the snake, and our results quantitatively support upgrading this species' threat level for extinction. This study can inform to programs to manage invasive snake populations and to conservation actions to recover the endemic lizard.